Effect of Solvents on the Adsorption Properties of Benzo[α]pyrene-imprinted Polymers - Bhagyashree Bhagat; Reddithota J. Krupadam (Adsorption Science & Technology)
Molecularly imprinted polymers (MIPs) specific for benzo[α]pyrene (B[α]P) have been synthesized in different solvents in order to study the corresponding morphological changes and adsorption properties. The adsorption capacities of the MIPs towards B[α]P were evaluated from the adsorption kinetics and isotherms. The lowest adsorption capacity (45 ng/mg) was found for MIP synthesized in chloroform, while MIP prepared in acetonitrile had the highest adsorption capacity. In order to complement the experimental observations, HyperChem software-based computer simulations were used to calculate the interaction energy between B[α]P and the functional monomer (methacrylic acid) in different solvents. The theoretical predictions correlated well with the experimental results and the method proposed in this study could be useful in the combinatorial screening of polymer precursors for the preparation of polymers with the desired properties. The presence of an organic solvent plays an important role in the formation of pores which, in turn, have a profound effect on the polymer adsorption properties.